2005
DOI: 10.1086/425952
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Mergers, Core Oscillations, and Cold Fronts

Abstract: We use numerical simulations with hydrodynamics to demonstrate that a class of cold fronts in galaxy clusters can be attributed to oscillations of the dark matter distribution. The oscillations are initiated by the off-axis passage of a low-mass substructure. From the simulations, we derive three observable morphological features indicative of oscillations: 1) The existence of compressed isophotes; 2) The regions of compression must be alternate (opposite and staggered) and lie on an axis passing through the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 19 publications
(36 reference statements)
8
102
0
Order By: Relevance
“…These cold fronts are difficult to reconcile with the remnant core interpretation and they are caused by the relative motion of low entropy gas of the cool core in the hotter outer gas. In the now dominant interpretation, this motion, dubbed sloshing by Markevitch et al (2001), is a consequence of the perturbation in the gravitational potential of the cluster that follows an off-axis minor merger (Tittley & Henriksen 2005;Ascasibar & Markevitch 2006). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cold fronts are difficult to reconcile with the remnant core interpretation and they are caused by the relative motion of low entropy gas of the cool core in the hotter outer gas. In the now dominant interpretation, this motion, dubbed sloshing by Markevitch et al (2001), is a consequence of the perturbation in the gravitational potential of the cluster that follows an off-axis minor merger (Tittley & Henriksen 2005;Ascasibar & Markevitch 2006). …”
Section: Introductionmentioning
confidence: 99%
“…A2142 hosts two "brightest cluster galaxies" (BCGs): one of them is close to the X-ray peak and therefore probably associated to the southern cold front, while the second one whose position would suggest an association with the Article published by EDP Sciences A44, page 1 of 16 A&A 556, A44 (2013) NW cold front, has a large peculiar velocity (v ∼ 1800 km s −1 Oegerle et al 1995), making its association with a merging subcluster that moves mainly on the plane of the sky unlikely (M00). When the sloshing mechanism was suggested to explain the presence of cold fronts in relaxed clusters, the striking similarity of the edges in the Chandra image of A2142 with the concentric arcs seen in simulation led to the change of the interpretation of cold fronts in this cluster as being caused by the sloshing of the core (Tittley & Henriksen 2005;Markevitch & Vikhlinin 2007). Recently, Owers et al (2011) studied the galaxy distributions in A2142 and, comparing it to the X-ray morphology, identified two candidate perturbers that could have induced the sloshing of the core and that move mainly along the line of sight.…”
Section: Introductionmentioning
confidence: 99%
“…Several simulations have also been employed to understand the origin of cold fronts in relaxed non-merging clusters (e.g. Churazov et al 2003;Tittley & Henriksen 2005;Ascasibar & Markevitch 2006).…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6]. Hydrodynamic simulations [9,2] have shown that such fronts can be caused by the sloshing of gas in the gravitational potential well caused by disturbances by passing subclusters. The process of sloshing brings hot, high-entropy gas at higher radii into contact with the cold, low-entropy gas of the core, resulting in the heating of the latter.…”
Section: Introductionmentioning
confidence: 99%